Optimization of Turn Around Time Calculation for C05-Check Aircraft Maintenance Using Critical Path Method (CPM) On Boeing 737-900er Aircraft - Islami, Alfi Daffa; Rahmawati, Fajar Khanif; Mulyani, Sri; Prakoso, Agung; Hartini, Dwi; Prattiwi, Elisabeth Anna (Institut Teknologi Dirgantara Adisutjipto, 2025)
Boeing 737-900 ER maintenance in Indonesia emphasizes timely, efficient routines to minimize risks. Using the Critical Path Method (CPM), the analysis calculates the Turn Around Time (TAT) for C05-Check maintenance. The CPM results estimate a TAT of 20.47 days (rounded to 20 days), while the company's data shows 21.73 days (rounded to 22 days), indicating a 2-day difference. This discrepancy highlights potential areas for improving maintenance efficiency. The TAT efficiency for the maintenance process is calculated at 0.057%. Optimizing mechanic workload based on this analysis can enhance turnaround times and ensure aircraft safety and operational scheduling. Accurate TAT predictions are vital for balancing maintenance quality with airline efficiency, making CPM a valuable tool in operational planning and resource allocation. Continued comparison with company data ensures maintenance practices remain precise, reducing unexpected delays and maintaining flight safety standards.